THE BAPEREIH COMPETITION: A SCORING SYSTEM IN GANDANG TASA OF PARIAMAN, WEST SUMATRA - Rovylendes , Adjuoktoza; Asril, Asril; Firman, Firman (Pena Cendekia Insani, 2025)
Bapereih is a competition between traditional gandang tasa groups in Pariaman. The scoring system records musical and non-musical errors made by the players. Musical errors include incorrect rhythm patterns, uncoordinated beats, and incorrect songs; non-musical errors include players not playing in unison, drumsticks/drummers falling, drum strings breaking or slipping, and drum skins tearing. This study aims to discuss the scoring system and criteria for bapereih gandang tasa in Pariaman. Data collection was carried out through careful observation and documentation of gandang tasa performances during bapereih, as well as interviews with performers and gandang tasa elders. Musical and non-musical errors were accumulated, with the lowest number of negative points determining the winner. Bapereih has become a distinct style with its own system and criteria in gandang tasa competitions in Pariaman. Bapereih serves as a model for preserving gandang tasa art and culture by maintaining the songs and playing techniques.